2003
DOI: 10.1592/phco.23.10.1175.32760
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Collaborative Care Model on Depression in a Primary Care Setting: A Randomized Controlled Trial

Abstract: To measure the effects of a collaborative care model that emphasized the role of clinical pharmacists in providing drug therapy management and treatment follow-up to patients with depression, we conducted a randomized controlled trial at a staff model health maintenance organization. We compared the outcomes of subjects treated in this collaborative care model (75 patients, intervention group) with subjects receiving usual care (50 patients, control group). After 6 months, the intervention group demonstrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
157
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 48 publications
3
157
0
2
Order By: Relevance
“…Despite having detected statistically significant differences in the degree of adherence to antidepressants, none of the previous studies found differences in clinical improvement (Adler et al 2004;Brook et al 2005;Capoccia et al 2004;Finley et al 2003;Rickles et al 2006). …”
Section: Discussionmentioning
confidence: 90%
“…Despite having detected statistically significant differences in the degree of adherence to antidepressants, none of the previous studies found differences in clinical improvement (Adler et al 2004;Brook et al 2005;Capoccia et al 2004;Finley et al 2003;Rickles et al 2006). …”
Section: Discussionmentioning
confidence: 90%
“…Characteristics and methodological quality of the included studies -Insert Table 1 -We identified 6 studies for inclusion in the analysis [26][27][28][29][30][31] which assessed pharmacist interventions in patients initiating or maintaining a treatment with antidepressant medication (Table 1).…”
Section: -Insert Figure 1 -mentioning
confidence: 99%
“…6 Pharmacists are frequently consulted for advice on psychotropic medications and there is consumer demand for advice on the use of these medications. 7,8 Medication counseling provided by pharmacists improves adherence to medications used for mental illnesses, 9,10 and pharmacist-led medication reviews may help identify and resolve psychotropic medication-related problems. 11 Pharmacists are among the most accessible health professionals.…”
Section: Introductionmentioning
confidence: 99%